Cochlear ribbon synapse maturation requires Nlgn1 and Nlgn3 - Miguel A. Ramirez; Yuzuru Ninoyu; Cayla Miller; Leonardo R. Andrade; Seby Edassery; Ewa Bomba-Warczak; Briana Ortega; Uri Manor; Mark A. Rutherford; Rick A. Friedman; Jeffrey N. Savas (iScience, 2022)
Summary: Hearing depends on precise synaptic transmission between cochlear inner hair cells and spiral ganglion neurons through afferent ribbon synapses.Neuroligins (Nlgns) facilitate synapse maturation in the brain, but they have gone unstudied in the cochlea. We report Nlgn3 and Nlgn1 knockout (KO) cochleae have fewer ribbon synapses and have impaired hearing. Nlgn3 KO is more vulnerable to noise trauma with limited activity at high frequencies one day after noise. Furthermore, Nlgn3 KO cochleae have a 5-fold reduction in synapse number compared to wild type after two weeks of recovery. Double KO cochlear phenotypes are more prominent than the KOs, for example, 5-fold smaller synapses, 25% reduction in synapse density, and 30% less synaptic output. These observations indicate Nlgn3 and Nlgn1 are essential to cochlear ribbon synapse maturation and function.